Synergistic effects from graphene and carbon nanotubes endow ordered hierarchical structure foams with a combination of compressibility, super-elasticity and stability and potential application as pressure sensors1. Issue 20 (28th May 2015) - Kuang, Jun; Dai, Zhaohe; Liu, Luqi; Yang, Zhou; Jin, Ming; Zhang, Zhong
<x xml:space="preserve">Abstract</x> Multi-scaled hierarchical architectures of graphene/CNT cellular solids endow materials with super elasticity, compressibility, stability and high specific strength.